Chemiexcitation in preventing macular degeneration - Brash, Douglas E.; Gaillard, Elizabeth R. (Frontiers in Photonics, 2024)
Quantum biology typically involves light exciting an electron to a higher energy state, or a magnetic field splitting a single state into several having different energies, or tunneling to flout the energy barrier between states. In chemiexcitation, electrons reach an excited state without light. A groundstate chemical reaction creates a reaction product born in the excited state, due to transient mixing between ground-and excited-state wavefunctions when the reaction intermediate molecule is twisted. We outline the chemiexcitation process and its biological triggers, describe the distinctive molecules susceptible to chemiexcitation, and review recent evidence that melanin in the human retina is chemiexcited as a strategy to prevent age-related macular degeneration.